Consideration of contribution of hot-electron injection to the resistive switching of sputter-deposited silicon oxide film - Yasuhisa Omura (Institute of Advanced Engineering and Science, 2021)
This paper considers the contribution of hot electrons to the resistive switching of sputter-deposited silicon oxide films based on experiments together with semi-2D Monte Carlo simulations. Using various device stack structures, this paper examines the impact of hot-electron injection on resistive switching, where conduction-band offset and fermi-level difference are utilized. Support is found for the predictions that hot-electron injection reduces the switching voltage and this should reduce the dissipation energy of switching. It is predicted that two-layer metal stacks can significantly reduce the number of oxygen vacancies in the sputter-deposited silicon oxide film after the reset process. It is also demonstrated that, in unipolar switching, the number of E’ or E” centers of the sputter-deposited silicon oxide film is relatively large.